2021
DOI: 10.3847/1538-3881/abf1ef
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Gravity Waves in the Middle Atmosphere of Mars

Abstract: Gravity waves are ubiquitous throughout the atmosphere of Mars. Their propagation and dissipation influence the circulation and thermal structure of the middle and upper atmosphere. Yet there have been few studies of gravity wave characteristics in the middle atmosphere, a region that is critical for their propagation from generation in the lower atmosphere to dissipation and associated exchanges of momentum and energy in the upper atmosphere. There have been few studies because few atmospheric profiles span t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…By comparing the original normalized temperature perturbation with the reconstructed one using the dominant wave amplitude in Figure 2(b), we can note that the extracted amplitudes and phases clearly portray the perturbation of the dominant wave. Also, note that the amplitudes of the wave-induced temperature perturbations are less than 15% of the mean background temperature and the mean vertical wavelengths are around 30 km, which are consistent with previous findings (Saunders et al 2021;Wu et al 2022b). Figures 2(c)-(d) are identical, but for orbit 9393 in MY35, with the tangent points of the occultation located at (161.5°W,25.2°S) and L s = 128°.8.…”
Section: Procedures For Extracting Gw Perturbations Fromsupporting
confidence: 90%
See 1 more Smart Citation
“…By comparing the original normalized temperature perturbation with the reconstructed one using the dominant wave amplitude in Figure 2(b), we can note that the extracted amplitudes and phases clearly portray the perturbation of the dominant wave. Also, note that the amplitudes of the wave-induced temperature perturbations are less than 15% of the mean background temperature and the mean vertical wavelengths are around 30 km, which are consistent with previous findings (Saunders et al 2021;Wu et al 2022b). Figures 2(c)-(d) are identical, but for orbit 9393 in MY35, with the tangent points of the occultation located at (161.5°W,25.2°S) and L s = 128°.8.…”
Section: Procedures For Extracting Gw Perturbations Fromsupporting
confidence: 90%
“…However, their results are confounded with the effect of thermal tides, due to the limitations of the data resolution. Saunders et al (2021) described the GWs in the middle atmosphere using 12 high-resolution atmospheric density profiles measured by ground-based stellar occultation and during atmospheric entry by landers and rovers. They found that the dominant wavelengths of GWs were 3-14 km and the amplitudes were 0.8%-2.5%.…”
Section: Introductionmentioning
confidence: 99%
“…The mesosphere of Mars is the region of the atmosphere from around 50–100 km and is currently one of the main regions of interest where several important atmospheric phenomena occur such as gravity waves (Nakagawa, Terada, et al., 2020; Saunders et al., 2021; Starichenko et al., 2021) and/or tides (England et al., 2019; Gröller et al., 2018; Jain et al., 2021; Nakagawa, Jain, et al., 2020). The mesosphere is the coldest region in the atmosphere of Mars and the temperature can be so low that CO 2 freezes into ice clouds (Liuzzi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The mesosphere of Mars is the subject of many recent studies related to tides (England et al., 2019; Jain et al., 2021; Nakagawa et al., 2020b), gravity waves (Saunders et al., 2021; Starichenko et al., 2021), CO 2 ice clouds (Liuzzi et al., 2021) and an intense warm layer present in the night side (Nakagawa et al., 2020a).…”
Section: Introductionmentioning
confidence: 99%